SIMULASI SISTEM KERJA BIOSEPTIC TANK BERBASIS DUA DIMENSI - Narti Narti; Sriyadi Sriyadi; Darul Annas Septihan; Mahmud Syarif (LPPM Universitas Bina Sarana Informatika, 2019)
In the business environment, especially in the business of selling a product, it definitely requires a user-friendly tutorial or instructions for using the product, the tutorial can be in the form of flow pictures or in the form of interactive two-dimensional (2D) or three-dimensional (3D) animation. The tutorial can function as a tool for introducing a product for buyers and potential buyers so that buyers' interest will increase and add buyer knowledge about the product. Now the author is encouraged to make a teaching aid using two-dimensional interactive animation that is user-friendly and interesting for PT. Global Core Fibertech. By using two-dimensional sketches to explain the product and use the video directly displayed the bioseptic tank's working system can allow customers to be interested in the product and not close the possibility that other competitors will gradually follow the animation method. With the design of the two-dimensional interactive animation, it is expected to increase the effectiveness, quality and intensity of its sales. With the technology used, the tools for making Adobe Flash CS6 as an application for making interactive animations, Adobe Photoshop CC as an application for making Bioseptic Tank and Actionscript sketches to move the animation process and application development methods used are Waterfall.